Wawasan Al-Qur’an Mengenai Metodologi Qur’ani dalam Penafsiran Kontemporer - Sadari (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2016)
The marginality of Islamic world in the scientific scene due to the lack of methodology. The only methodology that is found in Islam is ushul fiqh. However, ushul fiqhis no longer able to grow because it was regarded as something raw and can not be increased. In that context, the position of ushul fiqhis no longer as a methodology, but it would be a patent for each madzhableaders and its followers. Qur’anic methodology is expected to be used to bring Muslims to continue with varying views of contemporary ijtihad. Yet, it still based on the basic inspiration of the Qur’an as a major source and a guidance of the world and the hereafter. Qur’anic-based methodology here, referring to two prominent scholars of Islamic thought, Fazlur Rahman and Muhammad Shahrur. Fazlur Rahman offers a method of interpretation of the Qur’an which he called the theory of double movement. While, Muhammad Shahrur offers a method of interpretation of the Qur’an namely the theory of limits (hudud). Through interpretation of double movement and hudud theory, it is expected to create science revolutionary on the science of usul fiqh as a characteristic of methodology product of Muslims.